2006
DOI: 10.1002/bit.20828
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic differentiation of bovine bone marrow mesenchymal stem cells (MSCs) in different hydrogels: Influence of collagen type II extracellular matrix on MSC chondrogenesis

Abstract: Bone marrow mesenchymal stem cells (MSCs) are candidate cells for cartilage tissue engineering. This is due to their ability to undergo chondrogenic differentiation after extensive expansion in vitro and stimulation with various biomaterials in three-dimensional (3-D) systems. Collagen type II is one of the major components of the hyaline cartilage and plays a key role in maintaining chondrocyte function. This study aimed at analyzing the MSC chondrogenic response during culture in different types of extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
331
2
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(359 citation statements)
references
References 65 publications
(65 reference statements)
17
331
2
9
Order By: Relevance
“…Similarly, isolated MSCs can be directed to differentiate in vitro, by culture with lineage specific differentiation medium, to differentiate down the osteogenic, adipogenic and chondrogenic lineages (Gregory et al 2005). The fibroblast-like cells isolated from the spiny mice in this study exhibited multilineage differentiation potential with the capacity for adipogenic, chondrogenic and osteogenic differentiation, as demonstrated for MSCs isolated from other species (Bosnakovski et al 2006;Horwitz et al 2005;Izadpanah et al 2005;Eslaminejad et al 2006;Tuli et al 2003).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Similarly, isolated MSCs can be directed to differentiate in vitro, by culture with lineage specific differentiation medium, to differentiate down the osteogenic, adipogenic and chondrogenic lineages (Gregory et al 2005). The fibroblast-like cells isolated from the spiny mice in this study exhibited multilineage differentiation potential with the capacity for adipogenic, chondrogenic and osteogenic differentiation, as demonstrated for MSCs isolated from other species (Bosnakovski et al 2006;Horwitz et al 2005;Izadpanah et al 2005;Eslaminejad et al 2006;Tuli et al 2003).…”
Section: Discussionsupporting
confidence: 60%
“…MSCs are relatively easy to harvest, can be readily expanded in culture and, in addition to being isolated from a number of tissues, have also been isolated from a number of species including conventional rodents (Zangi et al 2006;Sung et al 2008), cows (Bosnakovski et al 2006) and horses (Vidal et al 2006). Typically, MSCs are isolated on the basis of plastic adherence, negative selection for a range of cell surface markers and multilineage differentiation potential.…”
Section: Introductionmentioning
confidence: 99%
“…The areas positive for Safranin-O/fast green and von Kossa staining were calculated using the Image J program from the images in Figs. 3 [32]. The addition of chondroitin sulfate (CS) in the polyethylene glycol (PEG)-based hydrogel also improved chondrogenic differentiation of goat MSCs and, notably, reduced the expression of collagen type X and Cbfa-1/Runx-2, which are involved in hypertrophic change of cartilage [33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating MSC differentiation down a chondrocytic lineage within porous scaffolds in the presence of TGF-β have been shown to induce MSC differentiation down a chondrogenic lineage (Jenner et al, 2007, Li et al, 2005, Chung and Burdick, 2008. In particular, a number of studies have shown that at 14 days, MSC differentiation and subsequent collagen type II gene expression was evident in the presence of TGF-β (Lee et al, 2008, Lisignoli et al, 2005, Bosnakovski et al, 2006, Park et al, 2009. Pellet culture systems are believed to be ideal culture environments to induce chondrogenesis due to the cell-cell contact which mimics the high cell density of embryonic cartilage development and maintains a chondrocytic phenotype (Fan et al, 2008, Chang et al, 2008, Zhang et al, 2010.…”
mentioning
confidence: 99%